Morphological Variations of Tongue Shape in Pediatric Patients Attending Dental OPD of Kanti Children’s Hospital, Nepal - Chaulagian, Rajib; Rai, Amita (Journal of Karnali Academy of Health Sciences, 2022)
Background: The morphology and surface features are characteristics of any individual and these are used for forensic identification too. For this purpose, tongue print has also been an important milieu for identification. This study was aimed to study the variations of tongue shape in pediatric patients visiting Kanti Children’s Hospital.Methods: A descriptive cross-sectional study was conducted among 224 pediatric patients visiting the dental outpatient department of Kanti Children’s Hospital, Maharajgunj, Kathmandu, Nepal. The patients were asked to protrude tongue in relaxed position, after which a photograph was taken and the tongue shape, borders and texture were evaluated. The study results were analyzed using descriptive statistical method with Statistical Package for Social Science (SPSS) version 16.Results: Total 224 children with the mean age 7.91 ±1.96 years participated in the study. Among the participants half of the participants were male. The U-shaped tongue was highly prevalent 137 (61.2%). Among the study population, 204 (91.1%) had smooth tongue and 206 (92%) had absence of fissures in the tongue. Among the participant’s, U shaped tongue was more in males than in females while V shaped tongue was more in females. Smooth border of the tongue was more in females (93%).Conclusion: From the present study, it can be concluded that variations of tongue were observed among gender in Nepalese pediatric population. The U shaped tongue was present more among male while V shaped tongue was more in female children.